The Influence Of Work-Life Balance And Work Motivation On Turnover Intention Through Compensation As An Intervening Variable Among Gen Z Employees In Bandar Lampung City - Satria Budi Utomo; Febrian Eko Saputro (Utan Kayu Publishing, 2025)
This study aims to examine the impact of work-life balance (WLB) and work motivation on turnover intention with compensation as an intervening variable among Generation Z employees in Bandar Lampung. The basis of this study stems from the high rate of job mobility among Gen Z who are sensitive to work-life balance, motivation, and reward schemes. The method employed is a quantitative study using a survey approach targeting 150 Gen Z respondents through a saturated sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), testing validity, reliability, multiple linear regression, determination coefficient, t-test, and F-test. The study results indicate that WLB and work motivation have a positive and significant influence on turnover intention and compensation. Compensation has a significant influence on turnover intention and is proven to mediate the relationship between WLB and work motivation toward turnover intention. The coefficient of determination (R²) reaching 65.6% indicates that this model can explain the majority of variations in the intention to change jobs. These results emphasize the significance of fair and flexible compensation, support for work-life balance, and enhanced work motivation in reducing turnover intention among Gen Z.